2017
DOI: 10.1016/j.neuropharm.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AMPA receptor and CaMKII activity in the lateral habenula reduces depressive-like behavior and alcohol intake in rats

Abstract: Depression is a well-known risk factor for developing relapse drinking, but the neuronal mechanisms underlying the interactions between depression and alcohol use disorders remain elusive. Accumulating evidence has associated depression with hyperactivity of the lateral habenula (LHb), an epithalamic structure in the brain that encodes aversive signals. Glutamate receptors contribute substantially to the excitability of LHb neurons. Glutamatergic synapses in LHb neurons largely express GluA1-containing α-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 49 publications
6
52
0
Order By: Relevance
“…Accumulating evidence indicates that the lateral habenula (LHb), an epithalamic structure in the brain, plays a crucial role in the aversive behaviors induced by many abused drugs, including alcohol [3][4][5][6][7][8][9] . Recently we demonstrated increased nociception 10,11 , anxiety-and depression-like behaviors 12,13 in alcohol-withdrawn rats. These aberrant behaviors are concomitant with increased activity of, and glutamatergic transmissions to, LHb neurons 12,13 .…”
Section: Introductionmentioning
confidence: 93%
“…Accumulating evidence indicates that the lateral habenula (LHb), an epithalamic structure in the brain, plays a crucial role in the aversive behaviors induced by many abused drugs, including alcohol [3][4][5][6][7][8][9] . Recently we demonstrated increased nociception 10,11 , anxiety-and depression-like behaviors 12,13 in alcohol-withdrawn rats. These aberrant behaviors are concomitant with increased activity of, and glutamatergic transmissions to, LHb neurons 12,13 .…”
Section: Introductionmentioning
confidence: 93%
“…Increases in LHb neuronal activity are not uniquely correlated with cocaine-induced withdrawal, but are also observed following exposure to ethanol. Withdrawal from ethanol (20% ethanol in a water bottle given intermittently 24 times over 8 weeks) increases spontaneous action potential firing and membrane excitability in LHb neurons measured using ex vivo brain slices (Li et al, 2016 , 2017 ). At the synaptic level, the AMPAR/NMDAR ratio and the frequency of sEPSCs are increased during ethanol withdrawal (Li et al, 2016 , 2017 ).…”
Section: Does Drug Withdrawal Alter Lhb Neuronal Function?mentioning
confidence: 99%
“…Withdrawal from ethanol (20% ethanol in a water bottle given intermittently 24 times over 8 weeks) increases spontaneous action potential firing and membrane excitability in LHb neurons measured using ex vivo brain slices (Li et al, 2016 , 2017 ). At the synaptic level, the AMPAR/NMDAR ratio and the frequency of sEPSCs are increased during ethanol withdrawal (Li et al, 2016 , 2017 ). Additionally, in an ethanol-induced conditioned taste aversion (CTA) paradigm, the basal firing in LHb neurons is increased in vivo when compared to neuronal firing pre-CTA (Tandon et al, 2017 ).…”
Section: Does Drug Withdrawal Alter Lhb Neuronal Function?mentioning
confidence: 99%
“…A recent study identified enhancement of AMPAR and CaMKII activity in LHb in alcohol withdrawal animals from chronic intermittent ethanol consumption with comorbidity of depression [21]. Suppression of AMPAR and CaMKII activity in the LHb improved depressive behavior and alcohol drinking and seeking behaviors.…”
Section: Dysregulation Of Ampar Camkii and Nmdar In Lhbmentioning
confidence: 98%
“…Since LHb neurons are almost all glutamatergic [20], GluA1-containing ɑ-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPAR), a subtype of ionotropic glutamate receptors, is largely expressed in glutamatergic synapses in LHb, which can be regulated by Ca 2+ /calmodulin-dependent protein II (CaMKII) [21]. AMPAR is composed of four subunits (GluA1-4) and the GluA1 subunit is expressed mostly in the LHb [22].…”
Section: Dysregulation Of Ampar Camkii and Nmdar In Lhbmentioning
confidence: 99%